from (A) we would know that 1 = a + b + c
from (b) we know 1 = -b((2a)
or b = -2a
from (c) we know that at the y-intercept x = 0
so 6 = 0 + 0 + c, so c=6
so back in the first equation
a+b+c = 1
a + (-2a) + 6 = 1
-a = -5
a + 5, then b = -10 and c=6
so f(x) = 5x^2 - 10x + 6
Pre-Calculus - "Given that f(x)=3x-4 g(x)=2x²+5 Find g(f(x))" Can you helpme out...
Maths - what is 0.1 of 240
maths - 35% of 20
s.s - please helpme thank you
helpme...............help - can any one tal me what is S&P....and exactly but ...
s.s - indus valley tools helpme please thanks
s.s (the middle ages) Grade 7 - what's for vassal i didn't got that one plaese ...
business math - 2/10, n/30 find the complement and net amount paid
math - Solve the following system of equations. x+y=13 22x+36y=356
English - Is there a webpage that will helpme figure out how to write a topic ...